المسؤولية الجزائية عن الأخطاء الطبية في التشريع الكويتي : دراسة مقارنة - شمار، خليفة غانم (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2021)
This thesis examined the phenomenon of medical malpractices in Kuwait's health care facilities in light of the Kuwaiti penal code provisions. This study aims to answer the following questions: what medical practices are considered ،according to the Kuwaiti legislation ،as malpractices? What is a medical error? Does the physician be responsible for all professional errors he commits? And what sort of errors can make a physician be held accountable under criminal liability provisions?. To answer these questions ،the researcher has relied mainly on the secondary data available in the library and on the internet. Methodologically، Inductive ،eplorative and comparative analysis are the main research approaches that being deployed in this research. This study constitutes of six chapters. The first chapter is the introduction that outlines the roadmap of this research. The second chapter provides a historical background on Kuwait and scrutinizes the real status of the health care sectors at the state in question. The third chapter deals with the key concept of medical practices ،conditions and ethics of practicing medical professions. ourth chapter identifies medical errors. Fifth chapter is on the criminal liability of the medical error. And the six chapter comprises of results and recommendations. Main results of this study are: there are medical malpractices in Kuwait ،but it is not spread at the level that makes it a phenomenon. the number of the lawsuit brought before the courts are neither projecting nor asserting the occurrence of medical errors ،it is solely due to the incapability of the layman in the Kuwaiti society to differentiate between the therapeutic complication and medical error. However، and for the approved medical malpractices، articles number 44 ،and 154 to 164 of the penal code provides the legal frme work for the judicial entities to resolve the dispute.